Wisdom's Wide Trajectory: Reading the Letter of James in Light of 4Qlnstruction - CASHELL MORAN, HELEN JOAN (Trinity College Dublin. School of Religions,Theology & Ecumenics. Discipline of Religions and Theology, 2019)
This Ph.D thesis reads James in light of 4QInstruction with the understanding that these two writings, in terms of their content and influence, represent two literary examples in which sapiential and apocalyptic elements are combined. The decision to include 4QInstruction is based on the pivotal role it has had in terms of compelling scholars to re-evaluate how the combination of these two categories is explained. 4QInstruction is framed in such a way throughout this thesis as to allow implications to be drawn for James. Therefore, James, a so-called ‘wisdom’ New Testament text is considered in light of a sustained study of the Second Temple sapiential tradition, and, particularly, its inclusion of apocalyptic. This thesis is structured in two parts. Part One comprises of Chapters One to Three and provides the context and justification for the study to follow. Chapter One traces the historical development of wisdom in terms of its overall theoretical framework and its generic existence. Chapter Two situates 4QInstruction in terms of the wisdom and apocalyptic debate, and begins to establish its significance for James. Chapter Three explores James in light of the expansion or development of the category of wisdom and its amalgamation of apocalyptic elements. This chapter highlights instances of the blending of the categorical lines between wisdom and apocalyptic in James in terms of its content, and begins to outline how this may improve our understanding of James. Part Two is made up of Chapters Four to Six, all of which emphasise the apocalyptic tradition’s affiliation with revealing of wisdom. Chapter Four studies the revealing of wisdom in James. The importance of the wisdom of James 1:5, and how the identification of its significance offers insight when it comes to other central aspects of James? teaching (e.g. the relationship between σοφία ἄνωθεν, νόµος, and λόγος, and the importance of not being enticed by one’s own ἐπιθυµία), are also highlighted. Chapter Five discusses the recipients of this wisdom. This is an important topic because it is the pursuit and living in accordance with σοφία ἄνωθεν that enables one to be included among God’s faithful community. Chapter Five hence asks: firstly, who is given revelation? Secondly, in terms of the faithful communities portrayed in James and 4QInstruction, is the language of ‘inclusion’ or ‘exclusion’ more appropriate? Chapter Six explores the closely associated topics of sin and evil in James, and the conceptions/traditions that may have influenced this author. This is important because James portrays humanity as having an apparent proclivity to sin and evil (i.e. Jas 1:8, 14; 4:8), and this assessment of humanity is pertinent to this thesis in terms of evaluating the potential obstructions one may experience in terms of their pursuit of wisdom. In conclusion, while others have noted that the categories of wisdom, eschatology, and apocalyptic are all present in both 4QInstruction and James, at present, no other work of this length exists that examines common analogies between these two writings in terms of their content, and the consequences these analogies may have for improving our overall understanding of James. This lacuna in biblical scholarship is the impetus of this study and what follows is one step in filling it.
APPROVED
Keywords: 4QInstruction, James, wisdom, apocalyptic, revelation